Develop Business strategy of Seyang Corporation Vietnam = Xây dựng chiến lược kinh doanh công ty TNHH Seyang corporation Việt Nam - Nguyễn, Thị Lệ Thu (2020)
The first thing is to systematize the theoretical and practical basis for developing a business strategy of the company. The second thing is to assess the current situation of Seyang Corporation Vietnam’s strategy in recent years. The final thing is to propose some ideas on business strategy development of Seyang Corporation Vietnam.